Faktor Risiko Penularan HIV/AIDS Pada Ibu Rumah Tangga Pasangan Migran DI Kabupaten Kuningan Tahun 2017 - Cecep Heriana; Icca Stella Amalia; Ahmad Ropii (Jurnal Ilmu Kesehatan Bhakti Husada: Health Sciences Journal, 2017)
HIV / AIDS is a global and national problem of increasing the number of cases in a group of mothers whose households are largely due to risky behavior of husbands who have unprotected sex with risky groups and can transmit HIV infections to their wives. The purpose of this research is to know the risk factor of HIV / AIDS incidence in migrant housewife couple in Kuningan Regency 2017. Quantitative research type with case control design. The subjects of this study were HIV positive and HIV negative housewives in Kuningan District. Samples 56 with a ratio of 1: 1 were 28 cases and 28 sampling controls using acsidental sampling technique with questionnaire instrument and observation sheet with chi square statistical test. (P = 0,592, OR = 1,333), knowledge (p = 0,558, OR = 1,5), condom use (p = 0,000, OR = 0,087). Educational, economic, unrelated knowledge and condom use are associated with HIV / AIDS transmission to migrant housewives. It is expected to increase the mass extension to housewives in Kuningan Regency